Prospects for the utilization of marine bioenergy for coastal and small islands in Indonesia - Asep Bayu (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2011)
Marine bioenergy is the use of marine biomass for energy resources either directly or indirectlyvia chemical preparation. The end bioenergy products that can be derived are biobriket frommangrove, biogas from macroalgae, biodiesel from microalgae and bintaro seed and bioethanolfrom seagrass and nipah palm. The advantages of marine bioenergy compared to those fromsolar and wind are its abundant supply of raw materials as well as the low cost and simplicity of itsenergy conversion technologies. Marine bioenergy is capable to cover three main sectors ofenergy needed by coastal communities. The supply of energy can be reassured since the conceptof energy harvesting can be applied to transform coastal regions into “Desa Mandiri Energy”.Cultivation of energy crops may also provide new employments and increase public awarenesson the importance of coastal marine biology resources. Therefore, marine bioenergy could be anideal alternative that supports not only energy security, but also social, economy, and ecologyaspects.